1991
DOI: 10.1210/endo-128-1-379
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Increases Lipolysis and the Number of β-Adrenoceptors in Male Rat Adipocytes*

Abstract: The influence of androgen status on the regulation of lipolysis and number of beta-adrenoceptors in isolated adipocytes was studied in male rats. Castration resulted in decreased catecholamine-induced as well as forskolin-induced lipolysis. beta-adrenoceptor number, examined by a whole cell cyanopindolol binding assay, was also diminished to a similar extent. Testosterone treatment of castrated rats normalized lipolysis as well as beta-adrenoceptor number. These results demonstrate that testosterone stimulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
94
2
6

Year Published

1993
1993
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(105 citation statements)
references
References 31 publications
3
94
2
6
Order By: Relevance
“…Androgens have been shown to exert a lipolytic action in adipocytes from rats (36). Accordingly, fatty acid turnover was increased in men treated with testosterone (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Androgens have been shown to exert a lipolytic action in adipocytes from rats (36). Accordingly, fatty acid turnover was increased in men treated with testosterone (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…32 Testosterone may mediate this effect because it has been shown to increase adipocyte badrenergic receptor expression. 33,34 Increased delivery of free fatty acids to the liver has been implicated in the reduced insulin clearance and dyslipidaemia associated with central obesity. 35 In summary, these studies have suggested that adipose tissue from the subcutaneous abdominal and intra-abdominal sites of women has different steroidogenic potentials which may be influenced by body weight.…”
Section: Discussionmentioning
confidence: 99%
“…2 On the other hand, low testosterone levels are responsible for higher body fat; in fact, testosterone, acting through a specific receptor, 3 has lipolytic effects in adipocytes; 4,5 moreover, in vivo studies performed in men have shown that testosterone supplementation causes a more rapid turnover of triglycerides in the subcutaneous abdominal adipose tissue region 6 and inhibits lipoprotein-lipase (LPL) activity and triglyceride uptake and assimilation, 6,7 these effects being prominent in the intraabdominal fat depot. 7 An inverse association has been found between plasma testosterone levels and the extent of coronary artery disease (CAD) in men with angina pectoris, thus suggesting that low testosterone levels may be a risk factor for CAD.…”
Section: Introductionmentioning
confidence: 99%